Catalogue of the mite families Ascidae Voigts & Oudemans, Blattisociidae Garman and Melicharidae Hirschmann (Acari: Mesostigmata) - Moraes, Gilberto J. De; Britto, Erika P.j.; Mineiro, Jefferson L. De C.; Halliday, Bruce (Zootaxa, 2016)
Until recently, mites in the families Ascidae, Blattisociidae and Melicharidae together constituted what was considered to be a single family, the Ascidae (sensu lato). We include all three families in this catalogue because of their many morphological similarities, as well as for historic and ecological reasons. Together with most Phytoseiidae and some Ameroseiidae, these are the only mesostigmatid mites commonly found on plants. In this publication we initially provide a historic overview of these groups, summarising the changes in the taxonomic concepts of the genera and other subfamilial taxa. This is followed by a thorough characterisation of each family and genus. A dichotomous key for the separation of families and genera is included. We then list the species considered to belong to these families, with details of the literature concerning the taxonomy of each species, and information about their type specimens and type localities wherever possible. The numbers of taxa considered as valid in this publication are: 372 species in 17 genera of Ascidae, 367 species in 14 genera of Blattisociidae, and 206 species in 11 genera of Melicharidae. We attempt to place each species in the most appropriate genus. In doing so, we propose 30 new combinations, including a species here transferred from Ascidae sensu stricto to Rhodacaridae. We propose five new names to replace junior homonyms, one new generic synonymy, and one new specific synonymy. Some species are insufficiently known and could not be reliably placed in any genus; these are listed as species incertae sedis. We also provide a list of species and genera that have been placed in these families at some time, but which have been transferred to other groups.